Quenching medium and quenching process for improving mechanical property of ZG40Mn2 material

By using water-based quenching media with components such as polyalkylene glycol and silver-carrying mesoporous silica and specific quenching processes in ZG40Mn2 material, the problems of high hardness and poor toughness and improper cooling speed due to temperature changes are solved. Its mechanical properties and toughness have been significantly improved.

CN119120849APending Publication Date: 2024-12-13ZUNYI JINYE MASCH FOUNDRY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411263372.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the quenching process, ZG40Mn2 material has high hardness and poor toughness due to too fast temperature changes, and improper cooling speed leads to quenching soft spots and cracks. The overall performance is poor and its mechanical properties need to be improved.

Method used

Using a water-based quenching medium composed of polyalkylene glycol, composite cold-speed adjustment additive, composite anti-rust agent, defoaming agent and water, through quenching processes corresponding to different casting temperatures, including normalization, annealing and quenching oil cooling Steps: Control the cooling speed to improve the mechanical properties of the material.

Benefits of technology

It significantly improves the mechanical properties of ZG40Mn2 material, especially toughness. Through the synergistic effect of polyalkylene glycol and silver-carrying mesoporous silica, high-temperature rapid cooling and low-temperature stable cooling are achieved, reducing deformation and cracking, and improving the product. Pass rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005036434930000071
    Figure BDA0005036434930000071
  • Figure BDA0005036434930000101
    Figure BDA0005036434930000101
Patent Text Reader

Abstract

The invention discloses a quenching medium and a quenching process for improving the mechanical property of a ZG40Mn2 material, and belongs to the technical field of alloy cast steel heat treatment, the quenching medium comprises the following raw materials by mass: 3% of polyalkylene glycol, 0.45% of a composite cooling rate adjusting additive, 0.1% of a composite antirust agent, 0.01% of an antifoaming agent, 0.035% of a preservative, and the balance of water; the quenching medium belongs to a water-based quenching medium, the maximum cooling speed is 331.2 DEG C / s, and the cooling speed below 300 DEG C is 99.5-102.3 DEG C / s. Compared with an existing water-based quenching medium, the cooling speed in the pearlite transformation stage is higher, the cooling speed in the martensite transformation stage is lower, and finally the mechanical property of the obtained ZG40Mn2 material is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy cast steel heat treatment, and in particular relates to a quenching medium and a quenching process for improving the mechanical properties of a ZG40Mn2 material. Background Art

[0002] ZG40Mn2 material is a low alloy cast steel, belonging to medium carbon quenched and tempered manganese steel, and is generally used in the quenched and tempered state. The strength and hardness of ZG40Mn2 steel castings are high, and the cutting performance and heat treatment process are good. They are widely used in wheel hubs, steering knuckles and other wheel assembly parts that are subject to friction. However, some steel castings often have to bear large impact loads during service, and brittle fractures may occur due to unstable crack expansion. Therefore, ZG40Mn2 material is required to have high toughness and plasticity to meet the use requirements.

[0003] The quenching process has a huge impact on ZG40Mn2 material. The quenching process includes quenching heating temperature, quenching insulation, and quenching cooling stages. If the quenching heating temperature and quenching insulation time are not properly controlled, the material changes too quickly with temperature, and the internal austenite grains are coarse, resulting in high hardness and poor toughness of the casting. Improper selection and use of quenching medium in the quenching cooling stage will result in too fast cooling speed in the low temperature stage (martensite transformation stage), which may easily lead to quenching cracks in the parts. The cooling speed is slow in the high temperature stage (pearlite transformation stage), and the parts are prone to quenching soft spots, resulting in poor overall performance. Therefore, seeking a quenching medium and quenching process that can improve the mechanical properties of ZG40Mn2 material is a technical problem that needs to be solved at present. Summary of the invention

[0004] The purpose of the present invention is to provide a quenching medium and a quenching process for improving the mechanical properties of ZG40Mn2 material, so as to solve the problem that the mechanical properties of the existing ZG40Mn2 material are poor.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A quenching medium for improving the mechanical properties of ZG40Mn2 material, comprising the following raw materials in mass percentage:

[0007] 3% polyalkylene glycol, 0.45% composite cooling rate adjusting additive, 0.1% composite rust inhibitor, 0.01% defoaming agent, 0.035% preservative, and the balance is water.

[0008] Furthermore, the average molecular weight of the polyethylene glycol is 30,000.

[0009] Furthermore, the composite cooling rate adjusting additive is composed of silver-loaded mesoporous silica, a first polyvinyl pyrrolidone and a second polyvinyl pyrrolidone in a mass ratio of 0.2-0.5:0.5-0.8:5.

[0010] Furthermore, the preparation steps of silver-loaded mesoporous silica are as follows:

[0011] Add amino mesoporous silica, methanol and silver nitrate aqueous solution into the reactor, stir for 8 hours in the dark, then add sodium borohydride aqueous solution dropwise, stir and react at 200-400r / min for 30 minutes, centrifuge, wash the precipitate with anhydrous ethanol and deionized water three times respectively, and freeze-dry for 48 hours.

[0012] Furthermore, the dosage ratio of the amino mesoporous silica, methanol, silver nitrate aqueous solution and sodium borohydride aqueous solution is 40 mg: 20 mL: 10 mL: 40 mL, the concentration of the silver nitrate aqueous solution is 0.3-0.8 g / L, and the concentration of the sodium borohydride aqueous solution is 9.46 g / L.

[0013] Furthermore, the particle size of the amino-modified mesoporous silica is 140-160 nanometers.

[0014] Furthermore, the average molecular weight of the first polyvinyl pyrrolidone is 1.3 million.

[0015] Furthermore, the average molecular weight of the second polyvinyl pyrrolidone is 58,000.

[0016] Furthermore, the composite rust inhibitor is composed of borax and sodium phosphate in a mass ratio of 1:1.

[0017] Furthermore, the defoaming agent is polyethylene glycol, and the molecular weight of the polyethylene glycol is 200-600.

[0018] Furthermore, the preservative is salicylic acid.

[0019] The quenching process of the quenching medium for improving the mechanical properties of the ZG40Mn2 material comprises the following steps:

[0020] S1. When the casting temperature of ZG40Mn2 product is ≤1580℃, ZG40Mn2 material product and ZG40Mn2 test bar are cast in the same furnace, and the cast ZG40Mn2 test bar and ZG40Mn2 material product are normalized, air-cooled, tempered, oil-cooled, and finally quenched and oil-cooled to obtain ZG40Mn2 finished product;

[0021] S2. When the casting temperature of ZG40Mn2 product is greater than 1580℃ and less than or equal to 1600℃, ZG40Mn2 material product and ZG40Mn2 test bar are cast in the same furnace, and the cast ZG40Mn2 test bar and ZG40Mn2 material product are annealed, then cooled with the furnace, normalized, air-cooled, tempered, oil-cooled, and finally quenched and oil-cooled to obtain ZG40Mn2 finished product;

[0022] S3. When the casting temperature of ZG40Mn2 product is greater than 1600℃, the ZG40Mn2 material product and the ZG40Mn2 test bar are cast separately and the casting temperature of the ZG40Mn2 test bar is ≤1600℃. When the casting temperature of the ZG40Mn2 test bar is ≤1580℃, the normalizing, air cooling, tempering, oil cooling and quenching oil cooling steps of step S1 are carried out. When the casting temperature of the ZG40Mn2 test bar is greater than 1580℃ and ≤1600℃, the annealing, air cooling, tempering, oil cooling and quenching oil cooling steps of step S2 are carried out.

[0023] Furthermore, in step S1, the tempering temperature is 850° C. and the tempering time is 180 min.

[0024] Furthermore, in step S2, the annealing temperature is 960° C. and the annealing time is 70 min.

[0025] Furthermore, in step S2, the tempering temperature is 580° C. and the tempering time is 84 min.

[0026] Furthermore, in step S1 and step S2, the normalizing temperature is 860° C., and the normalizing time is 70 min.

[0027] Furthermore, the quenching oil cooling process in step S1 and step S2 includes the following steps:

[0028] Heat up to 840℃, keep warm for 70min, transfer to quenching medium and keep for 10-15s, then keep warm at 585℃ for 180min, and finally oil cool.

[0029] Beneficial effects of the present invention:

[0030] The present invention provides a quenching medium for improving the mechanical properties of ZG40Mn2 material, which belongs to a water-based quenching medium and is composed of polyalkylene glycol, a composite cooling rate adjustment additive, a composite rust inhibitor, a defoaming agent, a preservative and water. The maximum cooling rate of the quenching medium is 331.2°C / s, and the cooling rate below 300°C is 99.5-102.3°C / s. Compared with the existing water-based quenching medium, the cooling rate is faster in the pearlite transformation stage and slower in the martensite transformation stage, so that the mechanical properties of the obtained ZG40Mn2 material are finally significantly improved. Specifically;

[0031] Due to its good reverse solubility, during the quenching process, when the temperature is higher than the cloud point of polyalkylene glycol, polyalkylene glycol precipitates and forms a solute film on the surface of the workpiece, thereby reducing the low-temperature cooling rate of water and reducing the deformation and cracking of the workpiece; when the temperature drops below the cloud point, the precipitated PAG dissolves again in water; the silver-loaded mesoporous silica and polyvinyl pyrrolidone in the composite cooling rate adjustment additive work synergistically, especially the deformation of the silver-loaded mesoporous silica at high and low temperatures due to the thermal expansion and contraction properties, resulting in the silver-loaded mesoporous silica contacting each other under high temperature conditions to form a thermal conductive network with good heat dissipation effect, effectively improving the cooling rate in the high temperature area, and cannot be connected into a thermal conductive network under low temperature conditions due to volume shrinkage, reduced contact area, and the barrier effect of the dispersant, significantly reducing the cooling rate in the low temperature area.

[0032] The present invention also provides a quenching process for improving the mechanical properties of ZG40Mn2 materials. According to the pouring temperatures of different ZG40Mn2 materials, corresponding quenching media are matched and different quenching processes are adopted to effectively improve the mechanical properties of ZG40Mn2 materials, especially toughness, and effectively improve the product qualification rate. DETAILED DESCRIPTION

[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the following examples and comparative examples:

[0035] Aminated mesoporous silica, with a particle size of 140-160 nm, was purchased from Xi'an Qiyue Biotechnology Co., Ltd.

[0036] The average molecular weight of the first polyvinyl pyrrolidone is 1.3 million.

[0037] The average molecular weight of the second polyvinyl pyrrolidone is 58,000.

[0038] Example 1

[0039] A method for preparing a quenching medium for improving the mechanical properties of ZG40Mn2 material comprises the following steps:

[0040] (1) Prepare the following raw materials in percentage by weight:

[0041] 3% polyalkylene glycol, 0.45% composite cooling rate adjusting additive, 0.1% composite rust inhibitor, 0.01% polyethylene glycol with a molecular weight of 200, 0.035% salicylic acid, and the balance is water;

[0042] (2) Add the raw materials in step (1) into a mixer and stir at 300 rpm for 1 hour to obtain a quenching medium that improves the mechanical properties of the ZG40Mn2 material.

[0043] The average molecular weight of the polyalkylene glycol is 15,000.

[0044] The composite cooling rate adjusting additive is composed of silver-loaded mesoporous silica, a first polyvinyl pyrrolidone and a second polyvinyl pyrrolidone in a mass ratio of 0.2:0.8:5.

[0045] The preparation steps of silver-loaded mesoporous silica are as follows:

[0046] Add 40 mg of amino-modified mesoporous silica, 20 mL of methanol and 10 mL of silver nitrate aqueous solution into the reactor, stir in the dark for 8 h, then add 40 mL of sodium borohydride aqueous solution dropwise, stir and react at 200 r / min for 30 min, centrifuge, wash the precipitate three times with anhydrous ethanol and deionized water respectively, and freeze-dry for 48 h. The concentration of the silver nitrate aqueous solution is 0.3 g / L, and the concentration of the sodium borohydride aqueous solution is 9.46 g / L.

[0047] The composite rust inhibitor is composed of borax and sodium phosphate in a mass ratio of 1:1.

[0048] Example 2

[0049] A method for preparing a quenching medium for improving the mechanical properties of ZG40Mn2 material comprises the following steps:

[0050] (1) Prepare the following raw materials in percentage by weight:

[0051] 3% polyalkylene glycol, 0.45% composite cooling rate adjusting additive, 0.1% composite rust inhibitor, 0.01% polyethylene glycol with a molecular weight of 400, 0.035% salicylic acid, and the balance is water;

[0052] (2) Add the raw materials in step (1) into a mixer and stir at 400 rpm for 0.8 h to obtain a quenching medium that improves the mechanical properties of ZG40Mn2 material.

[0053] The average molecular weight of the polyalkylene glycol is 30,000.

[0054] The composite cooling rate adjusting additive is composed of silver-loaded mesoporous silica, a first polyvinyl pyrrolidone and a second polyvinyl pyrrolidone in a mass ratio of 0.5:0.5:5.

[0055] The preparation process of silver-loaded mesoporous silica is the same as that in Example 1.

[0056] The composite rust inhibitor is composed of borax and sodium phosphate in a mass ratio of 1:1.

[0057] Example 3

[0058] A method for preparing a quenching medium for improving the mechanical properties of ZG40Mn2 material comprises the following steps:

[0059] (1) Prepare the following raw materials in percentage by weight:

[0060] 3% polyalkylene glycol, 0.45% composite cooling rate adjusting additive, 0.1% composite rust inhibitor, 0.01% polyethylene glycol with a molecular weight of 600, 0.035% salicylic acid, and the balance is water;

[0061] (2) Add the raw materials in step (1) into a mixer and stir at 500 rpm for 1 hour to obtain a quenching medium that improves the mechanical properties of ZG40Mn2 material.

[0062] The average molecular weight of the polyalkylene glycol is 30,000.

[0063] The composite cooling rate adjusting additive is composed of silver-loaded mesoporous silica, a first polyvinyl pyrrolidone and a second polyvinyl pyrrolidone in a mass ratio of 0.5:0.8:5.

[0064] The preparation steps of silver-loaded mesoporous silica are as follows:

[0065] Add 40 mg of amino-modified mesoporous silica, 20 mL of methanol and 10 mL of silver nitrate aqueous solution to the reactor, stir in the dark for 8 h, then add 40 mL of sodium borohydride aqueous solution dropwise, stir and react at 200-400 r / min for 30 min, centrifuge, wash the precipitate three times with anhydrous ethanol and deionized water respectively, and freeze-dry for 48 h. The concentration of the silver nitrate aqueous solution is 0.8 g / L, and the concentration of the sodium borohydride aqueous solution is 9.46 g / L.

[0066] The composite rust inhibitor is composed of borax and sodium phosphate in a mass ratio of 1:1.

[0067] Comparative Example 1

[0068] A method for preparing a quenching medium for improving the mechanical properties of ZG40Mn2 material, compared with Example 1, the difference is that the composite cooling rate adjustment additive consists of a first polyvinyl pyrrolidone and a second polyvinyl pyrrolidone in a mass ratio of 1:5.

[0069] Comparative Example 2

[0070] A method for preparing a quenching medium for improving the mechanical properties of a ZG40Mn2 material, compared with Example 1, differs in that the composite cooling rate adjustment additive is a first polyvinyl pyrrolidone.

[0071] Comparative Example 3

[0072] A method for preparing a quenching medium for improving the mechanical properties of a ZG40Mn2 material, compared with Example 1, differs in that the composite cooling rate adjustment additive is a second polyvinyl pyrrolidone.

[0073] Comparative Example 4

[0074] A method for preparing a quenching medium for improving the mechanical properties of a ZG40Mn2 material, compared with Example 1, differs in that the composite cooling rate adjustment additive is silver-loaded mesoporous silica.

[0075] According to GB / T 30823-2014 "Nickel Alloy Probe Test Method for Determining Cooling Performance of Industrial Quenching Oil", the cooling performance of the quenching medium in Examples 1-3 and Comparative Examples 1-4 was tested, and the test results are shown in Table 1:

[0076] Table 1

[0077]

[0078] It can be seen from the test results in Table 1 that the maximum cooling rate of the quenching medium obtained in Examples 1-3 is 331.2°C / s, and the cooling rate below 300°C is 99.5-102.3°C / s. Compared with Comparative Examples 1-4, the cooling rate is faster in the pearlite transformation stage and slower in the martensite transformation stage. It can be seen from the test results of Example 1, Comparative Example 2, Comparative Example 3, and Comparative Example 4 that the silver-loaded mesoporous silica and polyvinyl pyrrolidone in the composite cooling rate adjustment additive work synergistically.

[0079] Example 4

[0080] A quenching process for improving the mechanical properties of ZG40Mn2 material comprises the following steps:

[0081] The casting temperature of ZG40Mn2 product is 1580℃. ZG40Mn2 material product and ZG40Mn2 test rod are cast in the same furnace. The cast ZG40Mn2 test rod and ZG40Mn2 material product are normalized at 860℃ for 70min. After air cooling, they are tempered at 850℃ for 180min. Then they are oil cooled and finally quenched and oil cooled to obtain ZG40Mn2 finished product.

[0082] The quenching oil cooling process includes the following steps:

[0083] The temperature was raised to 840°C, kept at this temperature for 70 minutes, transferred to the quenching medium obtained in Example 1 and kept for 10-15 seconds, then kept at 585°C for 180 minutes, and finally oil-cooled.

[0084] Example 5

[0085] A quenching process for improving the mechanical properties of ZG40Mn2 material comprises the following steps:

[0086] When the casting temperature of ZG40Mn2 product is greater than 1590°C, ZG40Mn2 material product and ZG40Mn2 test rod are cast in the same furnace, and the cast ZG40Mn2 test rod and ZG40Mn2 material product are annealed at 960°C for 70 min, then cooled with the furnace, normalized at 860°C for 70 min, air cooled, tempered at 580°C for 84 min, oil cooled, and finally quenched and oil cooled to obtain ZG40Mn2 finished product.

[0087] The quenching oil cooling process includes the following steps:

[0088] The temperature was raised to 840°C, kept at this temperature for 70 minutes, transferred to the quenching medium obtained in Example 2 and kept for 10-15 seconds, then kept at 585°C for 180 minutes, and finally oil-cooled.

[0089] Example 6

[0090] A quenching process for improving the mechanical properties of ZG40Mn2 material comprises the following steps:

[0091] When the casting temperature of ZG40Mn2 product is 1600℃, ZG40Mn2 material product and ZG40Mn2 test rod are cast in the same furnace, and the cast ZG40Mn2 test rod and ZG40Mn2 material product are annealed at 960℃ for 70min, then cooled with the furnace, normalized at 860℃ for 70min, air cooled, tempered at 580℃ for 84min, oil cooled, and finally quenched and oil cooled to obtain ZG40Mn2 finished product.

[0092] The quenching oil cooling process includes the following steps:

[0093] The temperature was raised to 840°C, kept at this temperature for 70 minutes, transferred to the quenching medium obtained in Example 2 and kept for 10-15 seconds, then kept at 585°C for 180 minutes, and finally oil-cooled.

[0094] Comparative Example 5

[0095] A quenching process for improving the mechanical properties of ZG40Mn2 material. Compared with Example 4, the quenching medium in Example 4 is replaced by a product prepared in Comparative Example 1, and the remaining raw materials, processes and parameters are the same as Example 4.

[0096] Comparative Example 6

[0097] A quenching process for improving the mechanical properties of ZG40Mn2 material. Compared with Example 4, the quenching medium in Example 4 is replaced by a product prepared in Comparative Example 2, and the remaining raw materials, processes and parameters are the same as Example 4.

[0098] Comparative Example 7

[0099] A quenching process for improving the mechanical properties of ZG40Mn2 material. Compared with Example 4, the quenching medium in Example 4 is replaced by a product prepared in Comparative Example 3, and the remaining raw materials, processes and parameters are the same as Example 4.

[0100] Comparative Example 8

[0101] A quenching process for improving the mechanical properties of ZG40Mn2 material. Compared with Example 4, the quenching medium in Example 4 is replaced by a product prepared in Comparative Example 4, and the remaining raw materials, processes and parameters are the same as Example 4.

[0102] The mechanical properties of the finished ZG40Mn2 products obtained from Examples 4 to 6 and Comparative Examples 5 to 8 were tested, and a CMT7205 microcomputer-controlled universal testing machine was used to perform a tensile test on the samples. The test results are shown in Table 2:

[0103] Table 2

[0104]

[0105]

[0106] It can be seen from the test in Table 2 that compared with comparative examples 5-8, the ZG40Mn2 finished products obtained in examples 4-6 have better mechanical properties.

[0107] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0108] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A quenching medium for improving the mechanical properties of ZG40Mn2 material, characterized in that: Including the following raw materials by mass percentage: 3% polyalkylene glycol, 0.45% composite cooling rate adjusting additive, 0.1% composite rust inhibitor, 0.01% defoaming agent, 0.035% preservative, and the balance is water.

2. A quenching medium for improving the mechanical properties of ZG40Mn2 material according to claim 1, characterized in that: The average molecular weight of the polyalkylene glycol is 30,000.

3. The quenching medium for improving the mechanical properties of ZG40Mn2 material according to claim 1, characterized in that: The composite cooling rate adjusting additive consists of silver-loaded mesoporous silica, a first polyvinyl pyrrolidone and a second polyvinyl pyrrolidone in a mass ratio of 0.2-0.5:0.5-0.8:

5.

4. The quenching medium for improving the mechanical properties of ZG40Mn2 material according to claim 1, characterized in that: The preparation steps of silver-loaded mesoporous silica are as follows: Add amino mesoporous silica, methanol and silver nitrate aqueous solution to the reactor, stir in the dark for 8 hours, then add sodium borohydride aqueous solution dropwise, stir and react at 200-400 r / min for 30 minutes, centrifuge, wash the precipitate with anhydrous ethanol and deionized water three times respectively, and freeze-dry for 48 hours.

5. The quenching medium for improving the mechanical properties of ZG40Mn2 material according to claim 4, characterized in that: The dosage ratio of amino-modified mesoporous silica, methanol, silver nitrate aqueous solution and sodium borohydride aqueous solution is 40 mg:20 mL:10 mL:40 mL, the concentration of silver nitrate aqueous solution is 0.3-0.8 g / L, and the concentration of sodium borohydride aqueous solution is 9.46 g / L.

6. The quenching medium for improving the mechanical properties of ZG40Mn2 material according to claim 4, characterized in that: The particle size of amino-modified mesoporous silica is 140-160 nanometers.

7. The quenching medium for improving the mechanical properties of ZG40Mn2 material according to claim 4, characterized in that: The average molecular weight of the first polyvinyl pyrrolidone is 1.3 million, and the average molecular weight of the second polyvinyl pyrrolidone is 58,000.

8. The quenching process of the quenching medium for improving the mechanical properties of ZG40Mn2 material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. When the casting temperature of ZG40Mn2 product is ≤1580℃, ZG40Mn2 material product and ZG40Mn2 test bar are cast in the same furnace, and the ZG40Mn2 test bar and ZG40Mn2 material product obtained by casting are normalized, air-cooled, tempered, oil-cooled, and finally quenched and oil-cooled to obtain ZG40Mn2 finished product; S2. When the casting temperature of the ZG40Mn2 product is greater than 1580°C and less than or equal to 1600°C, the ZG40Mn2 material product and the ZG40Mn2 test bar are cast in the same furnace, the ZG40Mn2 test bar and the ZG40Mn2 material product obtained by the casting are annealed, then cooled with the furnace, normalized, air-cooled, tempered, oil-cooled, and finally quenched and oil-cooled to obtain the ZG40Mn2 finished product; S3. When the casting temperature of the ZG40Mn2 product is greater than 1600°C, the ZG40Mn2 material product and the ZG40Mn2 test bar are cast separately and the casting temperature of the ZG40Mn2 test bar is ≤1600°C. When the casting temperature of the ZG40Mn2 test bar is ≤1580°C, the normalizing, air cooling, tempering, oil cooling, and quenching and oil cooling steps of step S1 are performed. When the casting temperature of the ZG40Mn2 test bar is greater than 1580°C and ≤1600°C, the annealing, air cooling, tempering, oil cooling, and quenching and oil cooling steps of step S2 are performed. Among them, the quenching oil cooling process includes the following steps: Heat to 840℃, keep warm for 70min, transfer to quenching medium and keep for 10-15s, then keep warm at 585℃ for 180min, and finally oil cool.

9. The quenching process of the quenching medium for improving the mechanical properties of ZG40Mn2 material according to claim 8, characterized in that: The tempering temperature in step S1 is 850° C. and the tempering time is 180 min. The annealing temperature in step S2 is 960° C. and the annealing time is 70 min. The tempering temperature in step S2 is 580° C. and the tempering time is 84 min.

10. The quenching process for ZG40Mn2 material using a quenching medium for improving the mechanical properties of ZG40Mn2 material according to claim 8, characterized in that: In step S1 and step S2, the normalizing temperature is 860° C. and the normalizing time is 70 min.